Penerapan Penerapan Metode AHP dalam Menentukan Tingkat Kepuasan Pelanggan di Pratama Motor 2 - Putri Nabila (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2023)
Abstract – AHP is a method for ranking the best decision alternatives, when the decision maker has many objectives or criteria that must be met or consired. This method combines the strengths of the decision maker’s feelings and logic, then synthesizes various considerations into result that match the decision maker’s intuitive estimates as presented in the considerations that have been made. The end result of the AHP process is the priorities of the best criteria in decision making. This study aims to determine the results of decision making in determining the level of customer satisfactions using the Analytical Hierarchy Process (AHP) method. And the testing the calculations in this study using Expert Choice Software. Based on the results of the AHP analysis, it was concluded that sub-criterion D1, namely special attention to each customer, is the top priority for the sub-criteria with a value of 0,452 or 45,2%. And the lowest value is the Responsiveness criterion with a value of 0,156 or 15,6%. Keywords — AHP, Analytical Hierarchy Process , Customes Satisfaction,